HUBUNGAN ANTARA KESADARAN POSTUR ERGONOMIS DENGAN KEJADIAN NYERI PUNGGUNG BAWAH PADA MAHASISWA ITSK RS DR. SOEPRAOEN MALANG - Qhoirun Nisa; Sartoyo Sartoyo; Nurul Halimah; Angria Pradita (Kieraha Medical Journal, 2026)
Low Back Pain (LBP) is one of the most common musculoskeletal complaints among university students duet o academic activites that predominantly involve prolonged sitting. Ergonomic postural awareness serves as a protective factor by enabling individuals to maintain proper body posture in accordance with ergonomic principles, thereby reducing the risk of developing low back pain. This study aimed to analyze the relationship between ergonomic postural awareness and low back pain among students of ITSK RS dr. Soepraoen Malang. This study employed a cross-sectional design. The study population consisted of 323 active undergraduate nursing and physiotherapy students, with a sample of 135 respondents selected using a purposive sampling technique. Data were collected using the Postural Awareness Scale (PAS) to assess ergonomic postural awareness and the Visual Analog Scale (VAS) to measure the intensity of low back pain. Data analysis included the Kolmogorov–Smirnov normality test followed by the Spearman Rank correlation test. The results showed that most respondents had a moderate level of ergonomic postural awareness (54.1%) and mild low back pain (89.6%). The Spearman Rank correlation test demonstrated a significant relationship between ergonomic postural awareness and low back pain (p<0.001; r = -0.458), indicating that higher ergonomic postural awareness was associated with lower levels of low back pain among students. Therefore, ergonomic postural awareness serves as a protective factor in reducing the risk of musculoskeletal disorders among students who engage in prolonged static sitting.